A Comprenssive Survey On Different Methods For Detecting Salient Object (International Journal of Engineering and Computer Science, 2015)
This survey paper consists of various image processing techniques used for the detection of the salient region. The paper alsoincludes the comparative study of these techniques like precession recall analysis and the relative advantages and disadvantages. The majortopic of our interest is the Salient Region of the object which is an important factor in most of the areas like cognitive psychology andneurobiology. The various technique are different in there logic and performance the involved. Comparing to all the techniques on thereboth positive and negative sides the paper presented here is the best in my behalf to its domain knowledge